2007
DOI: 10.1074/jbc.m700270200
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Sterol Regulatory Element-binding Proteins and Liver Receptor Homolog-1 Reciprocally Suppresses Their Transcriptional Activities

Abstract: In previous studies it was demonstrated that sterol regulatory element-binding proteins (SREBPs) are able to interact with one of the nuclear receptors, hepatocyte nuclear receptor (HNF)-4, and that this interaction regulates transcriptional activities of these proteins (Misawa, K., Horiba, T., Arimura, N., Hirano, Y., Inoue, J., Emoto, N., Shimano, H., Shimizu, M., and Sato, R. SREBPs 3 are synthesized as membrane-bound precursor proteins and proteolytically processed to yield the N-terminal transcription fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 44 publications
2
26
1
1
Order By: Relevance
“…SF1 synergizes with several transcription factors, including GATA transcription factors (73)(74)(75)(76), cAMP regulatory element binding proteins (77)(78)(79), AP1 family members ( 80 ), and ␤ -catenin ( 81 ). Signifi cantly, the likelihood of a physical interaction between SF1 and SREBP1 is supported by studies demonstrating that both SREBP1 and SREBP2 interact with hepatic nuclear factor 4 ( 82 ) and with the liver receptor homolog (LRH)1 ( 83 ). LRH1 and SF1 belong to the NR5A subfamily of nuclear receptors and share greater than 90% conservation in the DNA binding domain and are >50% conserved in the ligand binding domain ( 71,84 ), so it is not surprising that SF1 also interacts with SREBP1.…”
Section: Discussionmentioning
confidence: 69%
“…SF1 synergizes with several transcription factors, including GATA transcription factors (73)(74)(75)(76), cAMP regulatory element binding proteins (77)(78)(79), AP1 family members ( 80 ), and ␤ -catenin ( 81 ). Signifi cantly, the likelihood of a physical interaction between SF1 and SREBP1 is supported by studies demonstrating that both SREBP1 and SREBP2 interact with hepatic nuclear factor 4 ( 82 ) and with the liver receptor homolog (LRH)1 ( 83 ). LRH1 and SF1 belong to the NR5A subfamily of nuclear receptors and share greater than 90% conservation in the DNA binding domain and are >50% conserved in the ligand binding domain ( 71,84 ), so it is not surprising that SF1 also interacts with SREBP1.…”
Section: Discussionmentioning
confidence: 69%
“…34) Kanayama et al demonstrated that sterol regulatory element-binding protein-2 (SREBP-2) bound to the DBD of LRH-1 leading to suppression of the coactivating effect of PGC-1a. 36) Ku proteins associated with the DBD in addition to the hinge region (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36] Safi et al showed that glucocorticoid receptor-interaction protein 1 (GRIP1) and peroxisome proliferator-activated receptor g coactivator-1a (PGC-1a) interacted with LRH-1 and enhanced its transactivation activity. They proposed that these coacitivators serve as "protein ligands" of LRH-1.…”
mentioning
confidence: 99%
“…Immunoprecipitation and Western blotting were performed as described previously (25,26). The signals on the membrane were quantified with an LAS1000 lumino image analyzer (FujiFilm).…”
Section: Immunoprecipitation and Western Blot Analysismentioning
confidence: 99%